New and Formerly Unknown Ormyridae Species from the United Arab Emirates (Hymenoptera, Chalcidoidea) - Zerova, M.D.; Seryogina, L.Ja.; Van Harten, A. (Вестник зоологии, 2012)
Three new species (Ormyrus qurrayahi Zerova, sp. n., O. punctellus Zerova, sp. n. and O. novus Zerova, sp. n.) are described. Two first species belong to diffinis species group (female gaster without dorsal median keel). O. novus sp. n. belongs to orientalis species group (female gaster with dorsal median keel). In addition, two Palaearctic species of the genus Ormyrus are recorded from the United Arab Emirates for the first time. A key to Palaearctic Ormyrus species is provided. Описаны три новых для науки видов хальцид семейства Ormyridae (Ormyrus qurrayahi Zerova, sp. n.; O. punctellus Zerova, sp. n. и O. novus Zerova, sp. n.), по материалам, полученным от А. ван Хартена (A. van Harten, United Arab Emirates). Первые два из указанных новых видов относятся к группе diffinis, у представителей которой брюшко самки не имеет дорсального продольного киля. O. novus sp. n. относится к группе orientalis, самки которого имеют продольный дорсальный киль на брюшке. Кроме того, для Объединённых Арабских Эмиратов указаны два палеарктических вида Ormyrus, ранее неизвестные с этой территории. Приведена таблица для определения палеарктических видов Ormyrus.